Fostering Village Governance: Formulating Regulations on Village-Owned Enterprises in Pabuaran Village, Serang Regency - Pipih Ludia Karsa; H. Ade Marpudin (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
To fulfill national priorities, especially